Pendampingan Digitalisasi Marketing UMKM Fahmi Jaya Kue - Siti Ning Farida; Rohma Kusuma Zulianti (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Digitalization has changed the way businesses operate in various sectors, including in marketing. MSMEs (Micro, Small and Medium Enterprises) often face challenges in adopting digital technology, especially in terms of marketing. Therefore, this study aims to investigate digital marketing assistance approaches that can help Fahmi Jaya Kue's UMKM in utilizing digital technology to improve their product marketing. This research method involves a qualitative approach by conducting in-depth interviews with the owner of UMKM Fahmi Jaya Kue and direct observation of the ongoing marketing process. The results of the study show that UMKM Fahmi Jaya Kue faces several challenges in implementing digital marketing, including limited knowledge of digital technology, limited human resources, and lack of access to effective digital platforms. To overcome this challenge, a holistic marketing digitalization assistance approach is proposed. This marketing digitalization assistance is expected to provide benefits to Fahmi Jaya Kue's MSMEs in increasing their marketing effectiveness, increasing customer reach, and increasing competitiveness in the digital era. This research can also provide insight for other MSMEs who wish to adopt digital marketing in their businesses.